THE IDIOSYNCRASY OF SYSTEMS IN COVID-19: REVIEW OF CURRENT KNOWLEDGE - Rohith Sharan Sankaran; Padmavathy K M; Kristina Sargsyan (Asian Journal of Medicine & Health Sciences, 2020)
The COVID-19 requires multidisciplinary approach in diagnosis and treatment as it involves multiple organ systems. This necessitates a need in understanding the involvement of each organ system in disease. This paper aims to capture and provide an overview of the associated symptoms of each system.